2007
DOI: 10.1002/mnfr.200600148
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of MAPK, Bcl‐2 family, cytochrome c, and caspases in induction of apoptosis by 1,6‐O,O‐diacetylbritannilactone in human leukemia cells

Abstract: 1,6-O,O-diacetylbritannilactone (OODBL) isolated from Inula britannica, exhibits potent antitumor activity against several human cancer cell lines. However, the molecular mechanism of OODBL in the induction of anticancer activity is still unclear. In the present study, we demonstrated that OODBL induced the occurrence of apoptosis in human leukemic (HL-60) cells and cell arrest at the S phase. On the other hand, activation of caspase-8, -9, and -3, phosphorylation of Bcl-2 and Bid, and increased release of cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…Cell‐cycle analysis revealed that AS induced cell‐cycle arrest at the G 2 ‐M phase, which is accompanied by an increase in sub‐G 1 fraction, indicating apoptotic cell death. Similar results were recently reported for the sesquiterpene lactone 1,6‐ O , O ‐diacetylbritannilactone in HL‐60 cells 28.…”
Section: Discussionsupporting
confidence: 90%
“…Cell‐cycle analysis revealed that AS induced cell‐cycle arrest at the G 2 ‐M phase, which is accompanied by an increase in sub‐G 1 fraction, indicating apoptotic cell death. Similar results were recently reported for the sesquiterpene lactone 1,6‐ O , O ‐diacetylbritannilactone in HL‐60 cells 28.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown that ABL exhibit potent anti-inflammatory effects in vascular smooth muscle cells 21, 22, 23 and anticancer activities against colon, breast, ovary, leukemia and prostate cancer cells. 24, 25, 26, 27 Moreover, additional researches reported that ABL could activate caspases via the mitochondrial apoptosis pathway, induce Bcl-2 phosphorylation and suppress NF- κ B activation in several types of cell lines. 21, 25, 27 Therefore, it is interesting to investigate whether ABL could be a synergist to help increase the efficacy of other chemopreventive agents in cancer therapy.…”
mentioning
confidence: 99%
“…24, 25, 26, 27 Moreover, additional researches reported that ABL could activate caspases via the mitochondrial apoptosis pathway, induce Bcl-2 phosphorylation and suppress NF- κ B activation in several types of cell lines. 21, 25, 27 Therefore, it is interesting to investigate whether ABL could be a synergist to help increase the efficacy of other chemopreventive agents in cancer therapy. With the goal of enhancing the chemopreventive effects of celecoxib and reduced the dose in chemotherapy, we evaluated the possibility of the combination treatment of celecoxib and ABL on human breast cancer in vivo and in vitro .…”
mentioning
confidence: 99%
“…In particular, relative stereochemistry was able to be assigned by Cheng et al (2012) through NOESY experiments. The NMR data are given in Table II from Inula britannica L. demonstrated strong cytotoxic activity and induction of apoptosis in HL-60 cells through the activation of caspase-8, -9, and -3, phosphorylation of Bcl-2 and Bid, and by augmenting the release of cytochrome c from mitochondria (Pan et al 2007). Acetylbritannilactone, also from Inula britannica, has enforced apoptosis in VSMC cells as shown by induction of a greater ratio of Bax/Bcl-2, activation of caspase-9, caspase-3, and the breakdown of Poly (ADP-ribose) polymerase .…”
Section: Resultsmentioning
confidence: 99%